Looking at the periphery from the suburbs: An information-structurally based taxonomy of Hanging Topics in German - Catasso, Nicholas (Linguistik Online, 2022)
In this paper, it is proposed on the basis of data from German that some of the information-structural features encoded by the projections located in the clause-internal Split-CP domain in the Rizzian (1997) model are replicated in the so-called “outer left periphery”, i. e. in the area situated above ForceP. In doing this, I pursue a cartographic approach in which information structure is directly represented in the syntax by means of syntactic heads that project within the clausal left periphery. The main claim of the paper is that the outer left periphery (of German) includes dedicated projections for four classes of topics, namely so-called “Contrastive Hanging Topics”, “Aboutness Contrastive Topics”, “Familiar Hanging Topics” and “Frame-setting Hanging Topics”. The observations made in this paper pave the way for a comparison with other languages, as well as for the question of the universality of this clause-peripheral makeup.